Can a Luxury Grocery Retailer Internationalise Without Diluting Its Brand Values? Fortnum & Mason and The Japanese Venture. - Drew, F. H. (2010)
The dissertation outlines the process of Internationalisation undergone by Fortnum & Mason (F&M) in their venture into the Japanese market. The predominant issue is to ascertain whether in doing so their brand values were diluted through the establishment of a joint venture (JV) in order to cater for this market. Control was shared between their Japanese partners, which presented the opportunity for miscommunication of values and objectives.